Experimental research on wall pressure distribution in C-D nozzle at Mach number 1.1 for area ratio 3.24 - Khan, Sher Afghan; Mokashi, Imran; Aabid, Abdul; Faheem, Mohammad (Blue Eyes Intelligence Engineering & Sciences, 2019)
In this experimental investigation, the work reported is about the influence of control on the flow field in the suddenly expanded duct at low supersonic Mach number. A Convergent-divergent (CD) nozzle was designed and fabricated out of brass material assembled with the suddenly expanded duct which was also made of brass material. At the re-circulation zone, the flow field was controlled by using the microjets of 1 mm diameter as an orifice and the control was arranged at an interval of 90 degrees at 6.5 mm from the central axis of the main jet. The measured wall pressure distribution was presented for Mach number 1.1 for the duct diameter of 18 mm leading to the area ratio 3.24. The L/D ratio of the duct was varied from 1 to 10, and the nozzle pressure ratio (NPR) considered for the experiments was from 3, 5, 7, 9 and 11. The present results have demonstrated that the microjets do not influence the flow field in the duct adversely and the flow field remained identical in the presence of control or absence of control.